Repercussões biopsicossociais de uma capacitação em atividades físicas em uma Unidade de Saúde da Família de São Carlos / SP - Melinski, Anita de Cássia (Universidade Federal de São Carlos, 2017)
The Family Health Strategy (ESF) aims to change the assistance standard, which is marked by curative actions, to a new way to offer care with emphasis in health promotion and prevention. However, physical activity, which is an essential component of these actions, is not always a common knowledge among the minimum ESF team. Therefore, with the implementation of the Support Nucleus to the Family Health Strategy, the Physical Education professional start to play a relevant role in general health practices, who is indicated to be present in the support team to the Family Health Unity (USF). This professional would provide the support to physical activity practices (PCAF), including for the other members of the team, since workplace expose the professionals to high levels of stress, which may affect negatively their performance. Nevertheless, until the present moment, literature regarding the long-term repercussions of an educational training to USF professionals were not found. The aim of this study was to analyse the three-year repercussions of physical-activity educational training offered to several professionals by a physical education professional in aspects related to physical activity in health and affectivity among professionals in an USF. This was a exploratory qualitative study. Nine USF professionals who had participated in a physical activity educational training were selected through multiple-types deliberated sampling. Semi-structured interviews were conducted three years after the end of the educational training. Content analysis was used to interpret the data, supported by caring the carer theoretical referential, which allowed the identification and comprehension of the repercussions due to the educational training. Professional health (physical, psychological and physiological) and affectivity (team union) were identified repercussions. The educational training conducted by a Physical Education professional lead to health and affectivity repercussions in professionals even after three years of the end of the proposal.
Keywords: Educação física e treinamento; Estratégia Saúde da Família; Promoção da saúde; Saúde do trabalhador; Physical education and training; Family Health Strategy; Health promotion; Occupational health; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA